ANALISIS PERLAKUAN AKUNTANSI PENDAPATAN JASA KONSTRUKSI DALAM RANGKA PENYAJIAN LAPORAN KEUANGAN SERTA DAMPAKNYA TERHADAP LABA PADA PT. TANDHANA QURNIA SANDIKA DI SAMARINDA - Sari, Neli Puspita (EKONOMIA, 2019)
Revenue, Financial Statement. The aim of study to be achieved in this research is to analyze and find out the accounting treatment of construction service revenue PT. Tandhana Qurnia Sandika in Samarinda is in compliance with the provisions of SAK ETAP No. 20, 2009 and to analyze and find out the accounting treatment of construction service revenue PT. Tandhana Qurnia Sandika in Samara resulted in an increase in theÂ acquisition of profitThe formulation of the problem in this study is what does PT. Tandhana Qurnia Sandika in Samarinda of the accounting treatment has been appropriated with a provisions of the Public Accountability without Entity of SAK ETAP No. 20, 2009 and what does PT. Tandhana Qurnia Sandika in Samarinda of the accounting treatment has an impact on increasing profitability. The theoretical basis used in this study is the completed contract method which is one of the construction contract methods that recognizes gross income and profit only when the contract has been completed. Hypothesis or provisional assumption in this study is the accounting treatment of construction services revenue by PT. Tandhana Qurnia Sandika not yet appropriate with a provisions of SAK ETAP No. 20, 2009 and then an impact on increasing profitability.This research uses is a descriptive comparative method in this method which gives an idea of an object or phenomenon with a way to compare with Standard contracts are completed and SAK ETAP No. 20, 2009. The results of this study indicate that construction service revenue recognition at PT. Tandhana Qurnia Sandika does not comply with the provisions of SAK ETAP No. 20, 2009 and the accounting treatment of construction service revenue PT. Tandhana Qurnia Sandika in Samara resulted in an increase in the acquisition of profit.